2018
DOI: 10.1152/ajprenal.00318.2018
|View full text |Cite
|
Sign up to set email alerts
|

Vesicles bearing gifts: the functional importance of micro-RNA transfer in extracellular vesicles in chronic kidney disease

Abstract: Extracellular vesicles (EVs), including microparticles (MPs) and exosomes (EXOs), are derived from a wide range of mammalian cells including blood platelets, endothelial cells, and kidney cells and can be detected in body fluids including blood and urine. While EVs are well established as diagnostic markers under pathophysiological and stress conditions, there is also mounting evidence of their functional significance as vehicles for communication between cells mediated by the presence of nucleic acids, especi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 163 publications
0
14
0
1
Order By: Relevance
“…In addition, platelet microparticles (PMPs) are increased in CKD and dialysis patients [91] and have been reported to express 50-to 100-fold more procoagulant capacity than activated intact platelets, with the ability to activate the classical complement pathway. The microRNAs carried by vesicles from platelets, endothelial cells, and monocytes have potential inflammatory effects [172]. Further, the gut dysbiosis in CKD may play a role in the thromboembolic complication in CKD.…”
Section: Uremia Platelet Dysfunction and Alterations In Immunitymentioning
confidence: 99%
“…In addition, platelet microparticles (PMPs) are increased in CKD and dialysis patients [91] and have been reported to express 50-to 100-fold more procoagulant capacity than activated intact platelets, with the ability to activate the classical complement pathway. The microRNAs carried by vesicles from platelets, endothelial cells, and monocytes have potential inflammatory effects [172]. Further, the gut dysbiosis in CKD may play a role in the thromboembolic complication in CKD.…”
Section: Uremia Platelet Dysfunction and Alterations In Immunitymentioning
confidence: 99%
“…Several studies have linked circulating EVs released from renal endothelial cells to the progression of different kidney diseases such as acute kidney injury, CKD, diabetic nephropathy (DN), lupus nephritis, and nephrotic syndrome [9][10][11]. As urine is also a rich source of EVs [12], increased levels of urinary EVs provide a possible noninvasive indicator of kidney injuries [12,13]. Indeed, Burger et al [14] reported that podocytes release EVs in vitro when treated with high glucose for 24 h. Interestingly, the same group detected significant increases in podocyte-EVs in type 1 diabetes patients in the absence of albuminuria, nephrinuria, or glomerular filtration rate (GFR) decline [15], implying that urinary podocyte-EVs may be a more sensitive marker for podocyte injury than proteinuria.…”
Section: Introductionmentioning
confidence: 99%
“…Although EVs appear to be associated with many diseases, their involvement in renal diseases (e.g., CKD) is especially strong (Tables 1 and 2). Several studies have also highlighted a major role for miRNA transported by EVs in CKD, as summarized by Abbasian et al [56]. Recently, Zietzer et al have identified an alteration of intercellular communication mediated by miRNA through EVs in CKD patients, thus promoting endothelial dysfunction [57].…”
Section: Evs and Ckdmentioning
confidence: 98%
“…Clinical and preclinical studies have highlighted the value of miRs (transported by EVs) as CKD biomarkers [56,106,[150][151][152][153][154][155][156][157][158][159]. Indeed, exosomes of patients with kidney diseases contain high levels of miR [152].…”
Section: Extracellular Vesicles As Biomarkers Of Ckdmentioning
confidence: 99%